HIGH PREVALENCE OF PREDIABETES AND VITAMIN D DEFICIENCY IN IBB GOVERNORATE, YEMEN: A CROSS-SECTIONAL STUDY - Al-Hetar, Mohammed A. M. Y.; Rusli, Noradliyanti; Kamaruzzaman, Mohd Amir; Ngah, Wan Zurinah Wan; Shah, Shamsul Azhar; Al-Matary, Abdullah Mohammed; Wahab, Norasyikin A. (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Prediabetes and vitamin D deficiency are growing health concerns linked to diabetes progression and its complications, yet their prevalence and association remain underexplored, specifically in Yemen. This study aims to assess the prevalence of prediabetes and vitamin D deficiency among individuals in the Ibb Governorate, Republic of Yemen. METHODOLOGY A cross-sectional study involving 1,046 participants who met study criteria was conducted across multiple centers in the Ibb Governorate, including Jiblah University for Medical and Health Sciences, Medical City Complex, and Al-Noor Hospital. Participants underwent HbA1c and serum vitamin D testing. Prediabetes was defined using American Diabetes Association criteria (HbA1c between 5.7% and 6.4%). Vitamin D levels <20 ng/mL were defined as deficient, and 20–30 ng/mL as insufficient. RESULT The prevalence of prediabetes was 25.7% (n = 269). The mean HbA1c and age were 5.9 ± 0.2% and 41.4 ± 10.2 years, respectively. Among the prediabetic group, 71.4% (n = 189) had vitamin D deficiency and 20.7% (n = 54) had vitamin D insufficiency — totaling 93.1% (n = 243) with suboptimal vitamin D levels. The mean ages for groups with deficiency, insufficiency, and sufficiency were 40.8 ± 9.9, 41.3 ± 10.0, and 47.8 ± 9.0 years, respectively. Vitamin D deficiency was slightly more prevalent in males (48.27%) than in females (44.83%). A significant age difference was observed between the sufficient group and both the deficiency (p = 0.01) and insufficiency (p = 0.04) groups. A Chi-square test revealed a significant association between gender and vitamin D status (χ² = 8.266, p = 0.01). CONCLUSION The significant prevalence of prediabetes and vitamin D deficiency in the Ibb Governorate underscores the need for comprehensive interventions addressing both conditions. Correcting vitamin D deficiency may reduce the progression from prediabetes to diabetes, potentially improving metabolic health outcomes and mitigating associated complications.